A Systematic Study of the Synthesis of 2ʹ-Deoxynucleosides by Mitsunobu Reaction - Seio, Kohji; Tokugawa, Munefumi; Kaneko, Kazuhei; Shiozawa, Takashi; Masaki, Yoshiaki (Synlett, 2017)
The Mitsunobu reaction has emerged as an important alternative for the preparation of synthetic 2′-deoxynucleosides, which have various biological and biotechnological applications. In this work, the Mitsunobu-based synthesis of 2′-deoxynucleosides was systematically studied. The effect of phosphine, azodicarbonyl reagent, and solvent on the product yield and α/β ratio was investigated, and the highest yield and β-selectivity were obtained using (n-Bu)3P and 1,1′-(azodicarbonyl)dipiperidine in DMF. The reaction was successfully applied to various nucleobase analogues.
Keywords: nucleoside synthesis; Mitsunobu reaction; N-glycosidation; stereoselectivity; solvent effects